On the Lathrobium fauna of China III. New species and additional records from various provinces (Coleoptera: Staphylinidae: Paederinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2013)
Material of the paederine genus Lathrobium Gravenhorst, 1802 from the Chinese provinces Sichuan, Chongqing, Beijing, Zhejiang, Fujian, and Jiangxi is examined. Twenty-two species are identified, two of them described previously and nineteen undescribed. Sixteen species are described and illustrated: Lathrobium celere sp. n. (Sichuan: Gongga Shan); L. ventricosum sp. n. (Sichuan: Gongga Shan); L. bibaculatum sp. n. (Sichuan: Erlang Shan); L. bispinigerum sp. n. (Sichuan: Erlang Shan); L. bihastatum sp. n. (Sichuan: Daxiang Ling); L. aspinosum sp. n. (Sichuan: Erlang Shan); L. appendiculatum sp. n. (southern Sichuan); L. fortepunctatum sp. n. (Chongqing: Jinfo Shan); L. jinfoicum sp. n. (Chongqing: Jinfo Shan); L. imminutum sp. n. (Beijing: Dongling Shan); L. parvitergale sp. n. (Zhejiang: Tianmu Shan); L. barbiventre sp. n. (Fujian: Wuyi Shan); L. depravatum sp. n. (Jiangxi: Wuyi Shan: Huanggang Shan); L. cornigerum sp. n. (Jiangxi: Wuyi Shan: Huanggang Shan); L. wuyicum sp. n. (Jiangxi: Wuyi Shan: Huanggang Shan); L. pium sp. n. (Guizhou: Leigong Shan). Four undescribed species from Sichuan, Zhejiang, Jiangxi, and Guizhou remain unnamed, since they are represented exclusively by females. The phylogenetic affiliations of the examined species are discussed. The localities where the newly described species were collected are mapped. Including the newly described taxa, 111 described Lathrobium species are currently known from mainland China.KeywordsColeoptera, Staphylinidae, Paederinae, Lathrobiina, Lathrobium, Palaearctic region, China, taxonomy, new species.Nomenclatural Actsappendiculatum Assing, 2013 (Lathrobium), spec. nov.aspinosum Assing, 2013 (Lathrobium), spec. nov.barbiventre Assing, 2013 (Lathrobium), spec. nov.bibaculatum Assing, 2013 (Lathrobium), spec. nov.bihastatum Assing, 2013 (Lathrobium), spec. nov.bispinigerum Assing, 2013 (Lathrobium), spec. nov.celere Assing, 2013 (Lathrobium), spec. nov.cornigerum Assing, 2013 (Lathrobium), spec. nov.depravatum Assing, 2013 (Lathrobium), spec. nov.fortepunctatum Assing, 2013 (Lathrobium), spec. nov.imminutum Assing, 2013 (Lathrobium), spec. nov.jinfoicum Assing, 2013 (Lathrobium), spec. nov.parvitergale Assing, 2013 (Lathrobium), spec. nov.pium Assing, 2013 (Lathrobium), spec. nov.ventricosum Assing, 2013 (Lathrobium), spec. nov.wuyicum Assing, 2013 (Lathrobium), spec. nov.